A Mild Juvenile Onset Canavan Disease With Atypical Clinical Presentation and MRI Brain Features - Preeya Rehsi; Ata Siddiqui; Rahul Singh; Obioma Ihezue; Rebecca Halligan (JIMD Reports)
ABSTRACT This case report highlights an atypical presentation of Canavan disease (CD) in a 13‐year‐old female with intention tremor and fine motor difficulties. Neuroimaging revealed symmetrical changes in various brain regions initially suggesting a neurometabolic or mitochondrial disorder. However, further investigations, including biochemical analysis and whole genome sequencing, confirmed a diagnosis of CD. Unlike classical presentations, this case exhibited milder symptoms and unusual MRI findings, contributing to the expanding clinical and radiological spectrum of CD. The importance of recognizing such atypical presentations is emphasized for accurate diagnosis and management of CD.